(untitled) (Ustozlar uchun, 2026)
One of dentistry’s biggest challenges is still the regeneration of periodontal tissues. Full structural healing is frequently not achieved by traditional treatments. In order to improve reparative processes, this study investigates a novel strategy that combines cellular technology—specifically, cultivated allogeneic fibroblasts—with osteoplastic materials (Geistlich Bio-Oss). Goal: Using a comparative histological analysis in an experimental model of periodontitis, assess the effectiveness of cultivated allogeneic fibroblasts in the regeneration of periodontal tissue.